The Challenges of Online Learning in Listening Class During Covid-19 Pandemic - Rini Susilowati (Edukasi Lingua Sastra, 2020)
Covid-19 pandemic has changed many aspects in human life worldwide. Some aspects such economy, social, politic, and education have been impacted by this pandemic. Education is one of crucial aspects that should be concerned. Learning activity has been conducting for several months not through face to face meeting but through online learning and other forms of learning. Some challenges appeared because online learning having some obstacles including in language learning activity of EFL class. This article tries to elaborates some challenges in conducting online learning in listening class at university level. The first challenge is related to the choosing of suitable technological devices, system and application used during the class. The second challenge is the packaging of material delivered so that it will be simplified but not to decrease the quality level of the material. The third challenge is the application of effective method and strategy suit to online learning in listening class. Besides the challenges which are discussed, the solution upon the challenges will be elaborated also in this article.